Bio-oil production from hydrothermal liquefaction of Pennisetum purpureum×Pennisetum typhoideum. (November 2022) - Katongtung, Tossapon; Phromphithak, Sanphawat; Onsree, Thossaporn; Tippayawong, Nakorn; Lauterbach, Jochen
Abstract: Among renewable and sustainable energy resources, biomass plays a vital role. Agricultural residues/wastes, energy crops, and lignocellulosic biomass could potentially be major feedstocks for biorefineries. In Thailand, one of the most interesting energy crops is hybrid giant Juncao grass (GJG) or Pennisetum purpureum × Pennisetum typhoideum . GJG can be easily grown and has relatively high yields under tropical climates. Herein, conversion of GJG to biofuels via hydrothermal liquefaction (HTL) was investigated using batch reactors under varying reaction temperatures of 250–350 °C and biomass-to-deionized water concentrations of 15–25 wt% at a fixed residence time of 30 min. Changes in temperature and GJG-to-deionized water concentration were found to markedly affect the yields and distribution of products from HTL of GJG. Yields of the liquid product, or bio-oil, can be up to 50 wt% at 350 °C and 25 wt% GJG-to-deionized water concentration. The yields of solid char and gas products fluctuated within 10–25 wt% and 30–45 wt%, respectively. Higher heating values of the resulting bio-oil and char were remarkably better than those of the raw material. An energy recovery of over 50% from the bio-oil, as well as about 35% from the char, can be obtained. By gas chromatograph-mass spectrometry and nuclear magnetic resonance, the bio-oil obtained was found to be a complex chemical mixture, consisting mainly of phenols, nitrogenous compounds, aliphatic compounds, ketones, carboxylic acids, and aldehydes. The finding is useful in future utilization of GJG via HTL for biofuel and/or biochemical production.